Evaluasi peningkatan pengetahuan tentang HIV/AIDS dan sikap terhadap ODHA di SMK Gelora Jaya Nusantara - Agustina, Dewi; Salsabila, Salsabila; Salsabilah, Khairani; Fadillah, Naya Kurnia; Najwa, Aqila; Nasution, Putri Suci Khoirunnisa; Nasution, Riri Andriani (JOURNAL of Public Health Concerns, 2025)
Background: HIV/AIDS remains a global health problem in Indonesia, with major barriers being misunderstandings, social stigma, and ineffective educational approaches. The level of knowledge of adolescents about HIV/AIDS is sufficient, but there are still many misconceptions and communication barriers that hinder open and effective education. HIV cases in Indonesia continue to increase, especially in the productive age group, including adolescents. It is essential to provide interactive, contextual, and stigma-free health education to improve adolescents' understanding of HIV/AIDS. Purpose: To evaluate the level of knowledge about HIV/AIDS and attitudes towards PLWHA among vocational high school students. Method: This activity uses a quantitative descriptive survey design that aims to assess the level of understanding and attitudes of students regarding HIV/AIDS at SMK Gelora Jaya Nusantara on January 9, 2025. The population is all students at SMK Gelora Jaya Nusantara, using purposive sampling based on certain criteria to obtain 43 students who were selected as respondents. Data collection used a closed questionnaire that was given directly to respondents. This questionnaire contains questions that measure students' knowledge, attitudes, and views regarding HIV/AIDS. Results: Obtaining data on respondents' knowledge and attitudes about HIV/AIDS transmission due to unsafe sexual intercourse, most of them strongly agree, namely 27 (62.8%), how to avoid HIV/AIDS transmission, most of them strongly agree, namely 23 (53.5%), the comfort of being friends with PLWHA has an opinion of agreeing as many as 13 (30.2%) and disagreeing 13 (30.2%). The majority of respondents strongly agree that HIV/AIDS can attack anyone, namely 27 (62.8%) and about the comfort of being friends with PLWHA based on gender, it shows that most male respondents agree as many as 8 (33.3%), while female respondents disagree and strongly disagree, each of which is 6 (31.6%). Conclusion: The level of understanding and basic knowledge of adolescents in Indonesia regarding HIV/AIDS is in a fairly good position, where most survey participants understand the definition, how it is transmitted, and preventive measures. There are psychosocial and cultural barriers that hinder open dialogue and the effectiveness of education, such as discomfort when discussing the issue and the existence of social stigma against people with HIV/AIDS. Formal information education does not have enough influence in increasing understanding of HIV/AIDS and fostering social empathy. Suggestion: More interactive, relevant, and stigma-free methods are needed so that adolescent knowledge about HIV/AIDS can increase significantly and reduce stigma and discrimination. It is hoped that the findings of this study will be the basis for developing a more effective educational approach that is in accordance with the social context of adolescents in schools and communities. Keywords: Adolescent education; HIV/AIDS; HIV knowledge; Stigma Pendahuluan: HIV/AIDS masih menjadi masalah kesehatan global di Indonesia, dengan hambatan utama berupa kesalahpahaman, stigma sosial, dan pendekatan pendidikan yang kurang efektif. Tingkat pengetahuan remaja tentang HIV/AIDS cukup, namun masih banyak miskonsepsi dan hambatan komunikasi yang menghalangi pendidikan yang terbuka dan efektif. Kasus HIV di Indonesia terus meningkat, terutama di kelompok usia produktif, termasuk remaja. Sangat penting untuk memberikan pendidikan kesehatan yang interaktif, kontekstual, dan bebas stigma untuk meningkatkan pemahaman remaja tentang HIV/AIDS Tujuan: Untuk mengevaluasi tingkat pengetahuan tentang HIV/AIDS dan sikap terhadap ODHA pada siswa/siswi SMK. Metode: Kegiatan ini menggunakan desain survei deskriptif kuantitatif yang bertujuan untuk menilai tingkat pemahaman dan sikap para siswa mengenai HIV/AIDS di SMK Gelora Jaya Nusantara pada tanggal 9 Januari 2025. Populasinya adalah semua siswa/siswi di SMK Gelora Jaya Nusantara, dengan menggunakan purposive sampling berdasarkan kriteria tertentu mendapatkan 43 siswa/siswi yang dipilih menjadi responden.  Pengumpulan data menggunakan kuesioner tertutup yang diberikan secara langsung kepada responden. Kuesioner ini berisi pertanyaan-pertanyaan yang mengukur pengetahuan, sikap, dan pandangan siswa/siswi mengenai HIV/AIDS. Hasil: Mendapatkan data pengetahuan dan sikap responden tentang penularan HIV/AIDS karena hubungan seksual tidak aman sebagian besar adalah sangat setuju yaitu sebanyak 27 (62.8%), cara menghindari penularan HIV/AIDS sebagian besar adalah sangat setuju yaitu sebanyak 23 (53.5%), kenyamanan berteman dengan ODHA memiliki pendapat setuju sebanyak 13 (30.2%) dan tidak setuju 13 (30.2%). Mayoritas responden berpendapat sangat setuju bahwa HIV/AIDS dapat menyerang siapa saja yaitu sebanyak 27 (62.8%) dan  tentang kenyamanan berteman dengan ODHA berdasarkan jenis kelamin menunjukkan sebagian besar responden laki-laki berpendapat setuju sebanyak 8 (33.3%), sedangkan responden perempuan berpendapat tidak setuju dan sangat tidak setuju yang masing-masing sebanyak 6 (31.6%). Simpulan: Tingkat pemahaman dan pengetahuan dasar remaja di Indonesia mengenai HIV/AIDS berada pada posisi yang cukup baik, dimana sebagian besar peserta survei memahami definisi, cara penularan, dan langkah pencegahannya. Terdapat hambatan secara psikososial dan kultural yang menghalangi dialog terbuka dan efektivitas pendidikan, seperti ketidaknyamanan saat membahas isu tersebut dan adanya stigma sosial terhadap orang dengan HIV/AIDS. Pendidikan berupa informasi secara formal tidak memiliki cukup pengaruh dalam peningkatan pemahaman tentang HIV/AIDS dan menumbuhkan empati sosial. Saran: Diperlukan metode yang lebih interaktif, relevan, dan bebas dari stigma agar pengetahuan remaja tentang HIV/AIDS dapat meningkat secara signifikan dan mampu menurunkan stigma serta diskriminasi. Diharapkan, temuan dari penelitian ini akan menjadi landasan untuk pengembangan pendekatan pendidikan yang lebih efektif dan sesuai dengan konteks sosial remaja di lingkungan sekolah dan masyarakat.